KORELASI ANTAR VARIABLE MONETER DAN FISKAL YANG MEMPENGARUHI JUMLAH KREDIT PERBANKAN DI INDONESIA - Khairani Khairani; Clarrissa Winata (POLITEKNIK LP3I JAKARTA, 2025)
This study aims to analyze the determinants of the amount of credit successfully distributed by banks and analyze the correlation between variables. The type of data used is secondary data collected using the documentation method. Data sourced from the Central Statistics Agency and the Financial Services Authority using monthly data from 2019-2024. The data analysis technique used is SEM PLS with the help of SmartPLS 3.8 software. All model criteria have been met in terms of Q square and GoF. The results of the BI rate hypothesis test have a positive and significant effect on banking ROA in Indonesia, while inflation and banking NPL show a significant negative effect on banking ROA, on the other hand there is not enough evidence that banking DPK has a significant effect on banking ROA. The results of the hypothesis test also show that banking DPK and banking ROA have a significant positive effect on the amount of investment credit and the amount of working capital credit in banking in Indonesia. Meanwhile, the results of the test for banking NPL in Indonesia show a significant positive effect on the amount of banking working capital credit, but do not have a significant effect on the amount of banking investment credit. The results of the Gross Domestic Product hypothesis test have a significant positive effect on banking DPK, while the Consumer Price Index shows no significant effect on DPK collected by banks in Indonesia.